1994
DOI: 10.1002/ijc.2910560311
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted agents and cervical neoplasia in colombia and Spain

Abstract: Case-control studies of cervical intra-epithelial neoplasia grade III (CIN III) and of invasive cervical cancer were carried out in Spain and Colombia to assess the relationship between cervical cancer and 6 common sexually transmitted agents (STAs). The CIN-III studies included 525 cases and 512 controls matched for age and for the place of recruitment; the invasive-cancer studies included 373 histologically confirmed cases of squamous-cell carcinoma and 387 age-stratified controls selected randomly from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0
6

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(54 citation statements)
references
References 20 publications
3
45
0
6
Order By: Relevance
“…Several seroepidemiologic studies have also found that C. trachomatis is a risk determinant for the development of cervical neoplasia. [7][8][9][10] The fact that our study was based on archival smears rather than fresh specimens might conceivably have resulted in some falsenegative results, e.g., if the DNA is degraded on storage. However, although the proportion of prediagnostic smears positive for HPV DNA decreased with increasing lag time (time until cancer was diagnosed), HPV positivity was not dependent on storage time (calendar time between smear taking and testing of the archival specimen), suggesting that there was no major degradation over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several seroepidemiologic studies have also found that C. trachomatis is a risk determinant for the development of cervical neoplasia. [7][8][9][10] The fact that our study was based on archival smears rather than fresh specimens might conceivably have resulted in some falsenegative results, e.g., if the DNA is degraded on storage. However, although the proportion of prediagnostic smears positive for HPV DNA decreased with increasing lag time (time until cancer was diagnosed), HPV positivity was not dependent on storage time (calendar time between smear taking and testing of the archival specimen), suggesting that there was no major degradation over time.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to C. trachomatis has been consistently associated with cervical cancer and its precursors. [7][8][9][10][11][12] However, this association has commonly been attributed to confounding by infection with HPV. Poor epidemiologic study designs and/or inaccurate diagnostic assays used have made it particularly difficult to disentangle the effects of these STIs.…”
mentioning
confidence: 99%
“…27 The HPV genotype strip contains 29 probe lines, detecting 27 individual HPV genotypes and two concentrations of the b-Globin control probe (All reagents were kindly provided by Roche Molecular Systems, Alameda, CA). The following types were detected: 6,11,16,18,26,31,33,35,39,40,42,45, 51 to 59, 66, 68, 73, 82, 83 and 84.…”
Section: Hpv Genotypingmentioning
confidence: 99%
“…1 Since the majority of cervical lesions regress to normal cytology after a period of 12 months from presumed first infection, it is thought that the remaining cervical lesions persist due to environmental, host and viral cofactors that have a pleiotropic effect on HPV viral replication, the immune system and tissue microenvironment. [2][3][4][5][6][7][8][9][10] Recent studies suggest that HPV16 viral load may be a possible molecular biomarker in the natural history of HPV infection. Using a semi-quantitative measure of HPV16 DNA levels, several observational studies have found a high correlation between high viral load and high-grade intra-epithelial lesions.…”
mentioning
confidence: 99%
“…50 In brief, antibodies to cytomegalovirus (CMV) were measured using an ELISA assay; 51 herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2) antibodies were detected with an ELISA assay based on a HSV-2 (gC2) antigen and on an HSV-1 and HSV-2 common type antigen; 51 and antibodies to Chlamydia trachomatis were ascertained using a microimmunofluorescence (MIF) test, 52 simplified to serotype L2.…”
Section: Serologymentioning
confidence: 99%